Label-free free-solution nanoaperture optical tweezers for single molecule protein studies. Issue 14 (3rd March 2015) - Al Balushi, Ahmed A.; Kotnala, Abhay; Wheaton, Skyler; Gelfand, Ryan M.; Rajashekara, Yashaswini; Gordon, Reuven
Abstract : Recent advances in nanoaperture optical tweezers have enabled studies of single nanoparticles like proteins in label-free, free-solution environments. Abstract : Nanoaperture optical tweezers are emerging as useful label-free, free-solution tools for the detection and identification of biological molecules and their interactions at the single molecule level. Nanoaperture optical tweezers provide a low-cost, scalable, straight-forward, high-speed and highly sensitive (SNR ∼ 33) platform to observe real-time dynamics and to quantify binding kinetics of protein–small molecule interactions without the need to use tethers or labeling. Such nanoaperture-based optical tweezers, which are 1000 times more efficient than conventional optical tweezers, have been used to trap and isolate single DNA molecules and to study proteins like p53, which has been claimed to be in mutant form for 75% of human cancers. More recently, nanoaperture optical tweezers have been used to probe the low-frequency (in the single digit wavenumber range) Raman active modes of single nanoparticles and proteins. Here we review recent developments in the field of nanoaperture optical tweezers and how they have been applied to protein–antibody interactions, protein–small molecule interactions including single molecule binding kinetics, and protein–DNA interactions. In addition, recent works on the integration of nanoaperture optical tweezers at the tip of optical fiber and in microfluidic environments are presented.